“Growth of Public Healthcare Services in Solapur District” (International Journal of Food and Nutritional Sciences, 2022)
Public healthcare system provides various healthcare services to needy people living in different geographical segmentations. Health is one of the very important component in the life which determine the productivity and efficiency of the people.Healthy life of the people helps to improve the longevity, physical appearance, mental health, brings happiness, boost the efficiency, prevent the diseases, develop the quality of health, leads productive life, enhance ability to perform activities and financial benefits. This research investigation has mainly progress of healthcare services, availability of beds and beds per lakh population in selected investigation area at given time period. This research investigation was based on the exploratory and descriptive research investigation. In this research study, researchers have used purely secondary data which was collected through the various articles, journals, thesis, books, magazines and websites.Researchers have found that growth rate of PHCs were higher than growth rate of hospitals in Solapur district over the period of time. Negative growth rate was found in dispensaries in selected investigation area at given time period. Total number of sub-centres were declined from 433 SCs to 429 SCs in Solapur district. But, it was very negligible.Researchers have also found that maximum number of PHCs and Beds were found in North Solapur as compare to other selected tehsils in Solapur district over the study period.